Consumer Behavior in the Choice of Mode of Transport: A Case Study in the Toledo-Madrid Corridor - Muro-Rodríguez, Ana I.; Perez-Jiménez, Israel R.; Gutiérrez-Broncano, Santiago (Frontiers in Psychology, 2017)
In general, most decisions that individuals make involve the choice of an alternative among a set of options. Within the context of the consumption of goods or services the decisions made by individuals involve the choice between a set of discrete alternatives, such as the choice of mode of transport. The methodology for analysis the consumer behavior used are the models of discrete choice based on the Theory of Random Utility. These models are based on the definition of preferences through a utility function that is maximized. These models also denominated of demand disaggregated derived from the decision of a set of individuals, who are formalized by the application of probabilistic models. The objective of this study is to determine the behavior of the consumer in the choice of a service, namely of transport services and in a short-distance corridor, such as Toledo-Madrid. The Toledo-Madrid corridor is characterized by being short distance, with high speed train available within the choice options to get to the airport, along with the bus and the car. And where offers of HST and aircraft services can be proposed as complementary modes. By applying disaggregated transport models with revealed preference survey data and declared preferences, one can determine the most important variables involved in the choice and determine the arrangements for payment of individuals. These payment provisions may condition the use of certain transport policies to promote the use of efficient transportation.